Kemampuan Literasi Digital Berbasis Merdeka Belajar Mata Kuliah Bahasa Indonesia Universitas Muhammadiyah Semarang - Yustinah, Yustinah; Hartono, Bambang (Jurnal Sastra Indonesia, 2023)
This research has the theme of Merdeka Belajar-based Digital Literacy Skill for Indonesian Language Course at Universitas Muhammadiyah Semarang. This research analyzed the Merdeka Belajar-based Digital Literacy Skill for an Indonesian language course, starting from the planning, implementing, and evaluating stages. The subjects consisted of 1184 students of Universitas Muhammadiyah Semarang who took the Indonesian Language course. They were 291 students from the Economic Faculty, 468 students from the Health Science faculty, 123 students from the Public Health faculty, 117 students from the Medicine Faculty, 99 students from the Dental Faculty, 51 students from the Language and Foreign Culture Faculty, and 35 students of Engineering Faculty. This descriptive statistic research collected the data from Google Forms. The results showed the planning aspect achieved 56.06%; the implementation aspect 60.435, and the evaluation aspect with 62.35%. The results showed that Merdeka Belajar-based Digital Literacy Skill for Indonesian Language Course at Universitas Muhammadiyah Semarang had balanced planning, implementation, and evaluation stages or aspects. This finding proved the balanced cognitive, psychomotor, theoretical, and digital literacy skill practices based on Merdeka Belajar for an Indonesian language course.